Watermelon as source of lycopene - Niizu, Patrícia Y. (2003)
This work had the objective of quantifying the principal carotenoids of the watermelon,cultivar Crimson Sweet, obtained from two producing states: São Paulo and Goiás. The samples were purchased during the year from the Central Distribution Center (CEASA) of Campinas, totalling five fruits analysed individually for each region. The analyses, carried out in duplicate, consisted of extraction with acetone, partition to petroleum ether and quantification by high performance liquid chromatography (HPLC) (C18 column, Spherisorb ODS2, 3 µm, 4.6 mm x 150 mm; isocratic elution, mobile phase of acetonitrilecontaining 0.05% triethylamine: methanol:ethyl acetate (60:20:20); flow rate of 0.8 mL/min), using external standardization. The HPLC chromatogram revealed that the watermelon analyzed contained almost exclusively lycopene, with a small amount of β-carotene. The lycopene and β-carotene contents (µg/g) were, respectively, 36 + 5 and 4.7 + 2.4 for the fruits from São Paulo, and 35 + 2 and 2.6 + 1.7 for those from Goiás. The concentrations of these two carotenoids resembled those found in tomato, cultivar Carmen (35 + 10 µg/g for lycopene and 3.2 + 0.6 µg/g for β-carotene), showing watermelon to be an important source of lycopene. The difference in terms of place of production was not significant...